2016
DOI: 10.1002/2016jb013305
|View full text |Cite
|
Sign up to set email alerts
|

Origin of intraplate volcanism in northeast China from Love wave constraints

Abstract: The tectonic source for widespread volcanism in northeast China has not been completely understood. We develop a 3‐D SH velocity model in NE China that provides new constraints to the origin of the volcanism. The 3‐D model is constructed from fundamental mode Love waves at the periods of 20–125 s recorded at 269 broadband seismic stations. The Changbai Mountain is characterized by a significant low velocity in the lower crust and uppermost mantle, which probably results from mantle upwelling due to the subduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
2
4
1
Order By: Relevance
“…The 3D seismic velocity model derived in this study is consistent with previous surface‐wave tomographic studies (e.g., Chen et al., 2021; Fan & Chen, 2019; Fu et al., 2016; Guo et al., 2016; Liu et al., 2017; Yang et al., 2019). For example, Fan and Chen (2019) reported a velocity reduction within the lower crust under the CBM.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The 3D seismic velocity model derived in this study is consistent with previous surface‐wave tomographic studies (e.g., Chen et al., 2021; Fan & Chen, 2019; Fu et al., 2016; Guo et al., 2016; Liu et al., 2017; Yang et al., 2019). For example, Fan and Chen (2019) reported a velocity reduction within the lower crust under the CBM.…”
Section: Discussionsupporting
confidence: 90%
“…However, neither our model nor most other seismic investigations corroborate such a thick lithosphere below the SLB. A recent P wave traveltime tomographic study (Jia et al., 2021) failed to detect the thin, high‐velocity lithosphere beneath the SLB, however, there is ample evidence from our study and a brunch of previous works (e.g., Fan & Chen, 2019; Fan et al., 2021; Fu et al., 2016; Li et al., 2012).…”
Section: Discussioncontrasting
confidence: 62%
“…Love‐wave inversion results show a notable low‐V zone at the bottom of the crust and the uppermost mantle beneath the Changbai volcano (Fu et al, ), suggesting the existence of a channel for magma migration beneath the volcano. The magmatic channel in the upper mantle beneath Changbai is not obvious in the previous ambient‐noise results (Kim et al, ; Wang & Chen, ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Guo et al () reported that the mantle upwelling beneath the CBV originates from the mantle transition zone and extends up to ~60 km below the surface, triggering the downwelling beneath the southern Songliao Basin to form small‐scale sublithospheric mantle convection. Large‐scale geophysical studies have yielded some fruitful results that commonly suggest that a deep source ascending from the mantle is responsible for the surface volcanism in the CBV (e.g., Fu et al, ; Guo et al, , ; Lei & Zhao, ; Tang et al, ; Zhao et al, ). These large‐scale seismic investigations image deep structures well beneath the CBV but lack fine resolution in shallow lithospheric structures.…”
Section: Introductionmentioning
confidence: 99%